Sub-national regionalisation of the AWARE indicator for water scarcity footprint calculations. (April 2020) - Boulay, Anne-Marie; Lenoir, Leo
Highlights: AWARE factors available for 3428 sub-national regions of the world. Higher spatial resolution than country scale, more applicable than watershed scale. Variability of country factors is high and enforces the use of sub-national factors. Abstract: In order to perform a Water Scarcity Footprint (WSF), as per the ISO standard 14, 046 (2014), it is necessary to multiply a volume of water consumed in a specific region, with the corresponding local water scarcity indicator. The use of these factors is recommended in priority at the native scale at which these factors were developed, which is the watershed scale. Alternatively, country-scale factors are provided to accommodate practitioners who may not have access to the exact watershed from which the water consumption they are assessing is located. However, such factors come with very large uncertainty. In several cases the practitioner may have access to a higher spatial resolution information, such as a state, province or department within one country. For this reason, the present work proposes sub-national AWARE factors for the entire globe, using sub-national borders, as an in-between resolution of watersheds and countries. Factors are provided for 3428 administrative regions, per month as well as annually, based on the three original weighted averages provided by AWARE: agri, non-agri and unknown. This scale is often more practical than the watershed scale, which may be more challenging to identify, and should lead to the use of a more-spatially resolved water footprint metric.